Analisis Saluran Pemasaran Dan Margin Pemasaran Kelapa Di Kelurahan Basabungan Kecamatan Pagimana: Analysis of Marketing Channels and Marketing Margins of Coconut in Basabungan Village Pagimana Distric - Klisman Tano; Heny Ariwijaya; Liswan Rusman (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2020)
The problem of marketing agricultural commodities is an interesting thing to study. Where the efficient marketing of agricultural products is a pre-condition for the smooth and balanced development of the agricultural sector. The purpose of this study was to determine the analysis of marketing channels and marketing margins in Basabungan Village, Pagimana District. This research was conducted in Basabungan Village, Pagimana District. The research was carried out for 6 months, from January to June 2019. The data used were primary data and secondary data using observation methods and direct interviews with farmers. Based on the research results, the marketing channels are as follows: Channel I: Farmers → collectors → small retailers → large retailers → final consumers. Channel II: Farmer's → small retailers' → large retailers → end consumers. Meanwhile, the marketing margin is as follows: At the farmer level by utilizing the services of collectors, the marketing margin is Rp. 842.14. By selling directly to small retailers, they get a marketing margin of Rp. 2,095.07, At the collector level, the marketing margin is Rp. 1,429.28, At the level of small retailers, the marketing margin is Rp. 2,442.87, At the wholesaler level, the wholesaler gets a marketing margin of Rp. 1142.89